How do you convert y=x-2y+x^2-3y^2 into a polar equation?

2 Answers
Dec 8, 2016

r=(sintheta-costheta+2sintheta)/(cos^2theta-3sin^2theta

Explanation:

for polar conversion

r^2=x^2+y^2

x=rcostheta

y=rsintheta

for

y=x-2y+x^2-3y^2

substituting from above.

rsintheta=rcostheta-2rsintheta+r^2cos^2theta-3r^2sin^2theta

cancelling and rearranging for ""r

cancel(r)sintheta=cancel(r)costheta- 2cancel(r)sintheta+cancel(r^2)^rcos^2theta-3cancel(r^2)^rsin^2theta

sintheta=costheta-2sintheta+rcos^2theta-3rsin^2theta

sintheta-costheta+2sintheta=rcos^2theta-3rsin^2theta

sintheta-costheta+2sintheta=r(cos^2theta-3sin^2theta)

r=(sintheta-costheta+2sintheta)/(cos^2theta-3sin^2theta

Dec 8, 2016

r=(3sin theta-cos theta)/(cos^2theta-3sin^2theta)

Explanation:

The conversion formula is (x, y)=r(cos theta, sin theta)

Making substitutions and reorganizing for the explicit form

r=(3sin theta-cos theta)/(cos^2theta-3sin^2theta)

This represents a hyperbola, with center at (-1/2, -1/2). See graph.

graph{x^2-3y^2+x-3y=0 [-2.5, 2.5, -1.25, 1.25]}